Tala ng kasaysayan ng pag-aalsa sa Pilipinas revolucion Filipina - Quintos, Felipe; Verceles, Lovelie V.; Orpilla, Melchor Espeleta 1971-; National Commission on Culture and the Arts (Philippines) (Intramuros, Maynila Pambansang Komisyon para sa Kultura at mga Sining, 2020)
History of revolution against the Spanish and American in the Philippines
Cover title
Tagalog and Pangasinan
Keywords: Pangasinan (Philippines) -- History -- 19th century; Philippines -- History -- Philippine American War, 1899-1902.; Philippines -- History -- Revolution, 1896-1898.; Zambales (Philippines) -- History -- 19th century